STUDENT MOTIVATION IN CHOOSING THE ENGLISH EDUCATION MAJOR AT THE FACULTY OF TADRIS AND TARBIYAH UIN FATMAWATI SUKARNO BENGKULU BASED ON COHORT 2024 - Etika Li (STKIP Subang, 2025)
This study aims to explore the motivations of students in choosing the EnglishEducation major at the Faculty of Tadris and Tarbiyah, UIN Fatmawati SukarnoBengkulu, cohort 2024, and to analyze their influence on academic achievement.This research employed a qualitative descriptive design using in-depth interviewswith three students representing both male and female perspectives, supported byobservations and relevant document studies. The findings reveal that studentmotivations differ according to gender: female students are primarily driven byintrinsic factors, such as personal interest in English, enjoyment of learning, andthe aspiration to become educators, while male students tend to emphasizeextrinsic factors, including career prospects, financial independence, and parentalsupport. Some students exhibit a combination of intrinsic and extrinsic motivations,where personal interest is reinforced by external encouragement. Motivation wasfound to significantly impact academic achievement: intrinsic motivation fostersdeep engagement, active participation, and additional learning efforts, whereasextrinsic motivation promotes goal-oriented behavior, discipline, and consistencyin completing assignments. Understanding these motivational differences and theireffects on academic performance is crucial for educators to design supportivelearning environments that meet diverse student needs and enhance overallacademic success.